Benzodiazepines “ the dimentions of use and misuse ” - Ali; Birsöz, Sunar (Journal of Dependence, 2000)
Benzodiazepines are the medications used to treat many of the frequent symptoms seen in medical practice and especially in psychiatry , including anxiety , insomnia , muscle spazms , epilepsy and other psychophysiologic disorders . They were recognized as safe and effective drugs by The World Health Organization ( WHO ) . After they were introduced on market in 1960’s , benzodiazepines replaced of barbiturates and meprobomates in the treatment of above disorders . In this review , we aim to make a summary about the effect and the efficacy of benzodiazepines and discuss the prejudice about themes on the light of current scientific literature.
Keywords: Benzodiazepines; indication; misuse; benzodiazepino - phobia